The Theory of Heinrich Christoph Koch and its role in the context of the analysis of musical works - Veljanovic, Jasna (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2018)
The relevance of the research. The musical theory of Heinrich Christoph Koch can serve as an example of an analytical music method that does not need to borrow methods and terminology from other sciences, as today is popular in the scientific discourse that relates to the analysis of a musical work. Definitions which are considered from the Musical Lexicon (Musikalisches Lexikon) are related to the musical form, the analysis of a musical piece, as well as its understanding from the composer’s viewpoint, beginning from his idea, through its development, right up to its realization. The aesthetic perception of a musical work – expressed through its elements and structure – is extremely important to Koch. Purpose of the paper. The purpose of the paper is the possible actualization of the analytical terminology from the Koch’s musical theory in modern analytical practice. Methods of research. The entries from the Musical Lexicon – which are the subject of consideration in this paper – are classified into two groups, in an overestimation from the way they are treated to a musical work. The first is connected with the idea and the plan of the musical piece and in it the Koch’s viewpoint to it (the piece) from the creative side is represented. The second group collected terms that relate to dissection, through which the work is viewed from an analytical point of view. Conclusions. Analytical terminology of Heinrich Christoph Koch is more suitable for analyzing Baroque musical forms of free (gallant) style because a lot of terms are used to analyze the same segment of a musical piece depending on what prevails in it (rhythm, melody, function, structure). This variety will provide a better analysis of a piece whose meaning is unavailable exclusively from the thematism, the concept on which most textbooks in musical form are written, and which is applicable to music, starting from Romanticism. Practical significance. This article is a part of a wider research with the goal of introducing this analytical terminology into today’s practice, especially to find the best analytical approach to music of Baroque and Classicism.